Analysis of Junior High School Students’ Errors in Solving Mathematical Problems for The Topic of Circle - Arief Budi Wicaksono; Adhetia Martyanti (Indonesian Journal of Mathematics Education, 2019)
This research aims to determine the type and percentage of errors that junior high school students do in solving math problems on the subject of the circles. This research is an expost facto research.  The population of this study is all students of grade VIII of one of the junior high schools in Purworejo as many as 182 students. Then by randomly selecting from the entire student, selected as many as 94 students as research samples. Research instruments are used in the form of diagnostic tests. Based on the results of the research, the students’ errors have done in solving math problems on the topic of circle are errors in comprehension (16,93%), transformation (27,39%), operation (26,30%), and drawing conclusion (71,55%). So, the most dominant error done by grade VIII students of one of the junior high schools in Purworejo is an error in the drawing of conclusions. Based on the results of this study, teachers need to design more effective learning to minimize the errors that occur, especially errors in drawing conclusions.